Operation and maintenance of irrigation sluice gates in tertiary canals - Wahyu Sejati; Elfrida Ratnawati; Grace Kurniawati Santoso; Bambang Endro Yuwono; M. Andreanov Amril; Fathya Khansa; Joan Arnold Fredrik (Universitas Muhammadiyah Magelang, 2022)
Kasemen District, Serang City, was one of the irrigation areas that experienced drought and became the focus of this community service. The lack of irrigation water is one of many factors that cause agricultural land in Kasemen District to switch functions. With the existence of several PKM activities such as field surveys, socialization, counseling on the operation and maintenance of irrigation sluice gates, it aims to increase community knowledge in the operation and maintenance of irrigation sluice gates. This activity encourages residents to be more concerned about river sustainability so that Cibomo Village's water needs can be met. The irrigation sluice gates are maintained as a result of this activity, and the Karya Tani Group's understanding of sluice gate operations and maintenance improves. Local residents are expected to become more concerned about the irrigation area environment as a result of the Karya Tani Group's increased understanding, particularly regarding the pattern of operation and maintenance of sluice gates.